Soil Organic Carbon Pool and the Production of Goji Berry (Lycium barbarum L.) as Affected by Different Fertilizer Combinations Under Drip Fertigation - Wang, Fang; Li, Wenhui; Lin, Yanmin; Nan, Xiongxiong; Yuan, Jingjing (Frontiers in Environmental Science, 2022)
Goji berries (Lycium barbarum L.) widely planted in arid to semi-arid regions are a functional resource characterized by a homology of medicine and food. Changing extensive water and fertilizer management practices to drip fertigation is one of the most cost-effective ways to achieve the sustainable development of Goji berry industry. This study explored the effects of different fertilizer combinations on the soil organic carbon pool and L. barbarum yield under drip fertigation in Ningxia, northwestern China. A two-year field experiment (2017–2019) was conducted using different levels of drip nitrogen (40, 60, and 80 mg L-1) and phosphorus (10, 20, and 30 mg L-1) fertigation. Compared with traditional manual fertilization (control), soil organic carbon contents in the 0–20, 20–40, and 40–60 cm layers increased by 33.6–144.4, 39.6–136.8, and 14.0%–73.6%, respectively, across all fertigation treatments. With increasing levels of fertigation, the easily oxidizable organic carbon content increased most prominently in the 0–20 cm soil layer and reached the highest value (538 mg kg-1) under treatment with 60 mg L-1 nitrogen plus 10 mg L-1 phosphorus. The microbial biomass carbon contents in the 20–60 cm soil layer was markedly higher under treatment with 60 mg L-1 nitrogen plus 30 mg L-1 phosphorus compared with other treatments. Fertigation increased the soil carbon pool management index and L. barbarum yield. The highest two-year average yield (13,890 kg ha-1) was obtained under treatment with 60 mg L-1 nitrogen plus 30 mg L-1 phosphorus. These findings suggest that drip fertigation with 60 mg L-1 nitrogen plus 30 mg L-1 phosphorus is the optimal practice for carbon sequestration and sustainable production of L. barbarum in the arid region.